A Multicentre Trial of Patient specific Rehearsal Prior to EVAR: Impact on Procedural Planning and Team Performance. (March 2017) - Desender, L.; Van Herzeele, I.; Lachat, M.; Duchateau, J.; Bicknell, C.; Teijink, J.; Heyligers, J.; Vermassen, F.; ,
Abstract : Objective: Patient specific rehearsal (PsR) prior to endovascular aneurysm repair (EVAR) enables the endovascular team to practice and evaluate the procedure prior to treating the real patient. This multicentre trial aimed to evaluate the utility of PsR prior to EVAR as a pre-operative planning and briefing tool. Material and methods: Patients with an aneurysm suitable for EVAR were randomised to pre-operative or post-operative PsR. Before and after the PsR, the lead implanter completed a questionnaire to identify any deviation from the initial treatment plan. All team members completed a questionnaire evaluating realism, technical issues, and human factor aspects pertinent to PsR. Technical and human factor skills, and technical and clinical success rates were compared between the randomised groups. Results: 100 patients were enrolled between September 2012 and June 2014. The plan to visualise proximal and distal landing zones was adapted in 27/50 (54%) and 38/50 (76%) cases, respectively. The choice of the main body, contralateral limb, or iliac extensions was adjusted in 8/50 (16%), 17/50 (34%), and 14/50 (28%) cases, respectively. At least one of the abovementioned parameters was changed in 44/50 (88%) cases. For 100 EVAR cases, 199 subjective questionnaires post-PsR were completed. PsR was considered to be useful for selecting the optimal C-arm angulation (median 4, IQR 4-5) and was recognised as a helpful tool for team preparation (median 4, IQR 4-4), to improve communication (median 4, IQR 3-4), and encourage confidence (median 4, IQR 3-4). Technical and human factor skills and technical and initial clinical success rates were similar between the randomisation groups. Conclusion: PsR prior to EVAR has a significant impact on the treatment plan and may be useful as a pre-operative planning and briefing tool. Subjective ratings indicate that this technology may facilitate planning of optimal C-arm angulation and improve non-technical skills. Trial registration: URL://www.clinicaltrials.gov . Unique identifier:NCT01632631 .